Design and Implementation of One Map Platform for Water Conservancy Spatial Planning - YANG Chuhua; XU Bing; CHEN Yubing; ZHANG Bo; JIANG Maoxi (Renmin Zhujiang)
According to the central government on unified planning system,establishment of land and space planning system and relevant deployment for supervision and implementation,problems such as inconsistent basic data for preparation of water conservancy planning,non-standardized format of submission results for water conservancy planning,difficulty in connection and coordination of multi-level water conservancy planning results,poor performance of aggregation and demonstration of water conservancy planning results,etc.,are better solved.This study utilizes Big data,3S,VR and other new generation information technology to construct a map platform for water conservancy spatial planning,develop function modules such as large data portal in time and space,auxiliary audit of planning results,management of planning results,display of planning aggregation,statistics and post-evaluation,and realize auxiliary audit,evaluation and visual expression of water conservancy planning data on one map.To realize the integrated management of water planning from the planning,implementation,post evaluation,life cycle,to provide the key technical means for the water conservancy spatial planning business objectives of “working basis from the diagram,working process to map synergy,work results to map”,and ultimately improve the level of refinement and intelligence of water conservancy planning and management.